2014
DOI: 10.1097/hjh.0000000000000012
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oral Contraceptive pills and the natural menstrual cYCLe on arterial stiffness and hemodynamICs (CYCLIC)

Abstract: OCP use was associated with significant increases in aortic and peripheral blood pressures, but not with increased arterial stiffness. Given the widespread OCP use, future longitudinal studies are needed to confirm our findings and assess the long-term effect of OCPs on arterial stiffness and hemodynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 45 publications
4
24
1
Order By: Relevance
“…To our knowledge, only three studies have examined arterial stiffness in relation to estrogen contraceptive use. As was the case in our population (Table 1), one of the studies found a higher PWV among estrogen contraceptive users [46], while two studies [47,48] found no such difference. In summary, any possible estrogen effect on vascular status measures is likely subtle in premenopausal women.…”
Section: Discussionsupporting
confidence: 82%
“…To our knowledge, only three studies have examined arterial stiffness in relation to estrogen contraceptive use. As was the case in our population (Table 1), one of the studies found a higher PWV among estrogen contraceptive users [46], while two studies [47,48] found no such difference. In summary, any possible estrogen effect on vascular status measures is likely subtle in premenopausal women.…”
Section: Discussionsupporting
confidence: 82%
“…Our study has several strengths, including the objective measurement of physical activity, the use of a validated measure of arterial stiffness, with which we have extensive experience in our Vascular Lab [22,4851], and our ability to account for a variety of demographic factors, and also specific antihypertensive, antihyperglycemic, and lipid-lowering therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the micromanometer records radial (peripheral) pressure waveforms, which are averaged and mathematically transformed using a generalized transfer function to derive an aortic (central) waveform . Mean arterial pressure (MAP), heart rate, and central AIx (cAIx) were also determined using the SphygmoCor software system …”
Section: Methodsmentioning
confidence: 99%
“…16 Mean arterial pressure (MAP), heart rate, and central AIx (cAIx) were also determined using the SphygmoCor software system. [17][18][19] Covariates A history of physician-diagnosed stroke, myocardial infarction, chest pain, and renal disease was assessed by questionnaires. Participants who had been diagnosed with at least one of the above health conditions were classified as having one or more comorbidities.…”
Section: Hypertension Assessment and Bp Measurementsmentioning
confidence: 99%